Outcomes in Men From the NHS Abdominal Aortic Aneurysm Screening Programme With a Large Aneurysm Referred for Intervention. (February 2021) - Meecham, Lewis; Jacomelli, Jo; Davis, Meryl; Pherwani, Arun; Lees, Tim; Earnshaw, Jonothan J.
Abstract : Objective: The NHS Abdominal Aortic Aneurysm Screening Programme (NAAASP) has been implemented since 2013. Men with a large aneurysm >54 mm, either at first screen or during surveillance, are referred for intervention. The aim of the present study was to explore outcomes in these men and to see whether there was any regional variation in treatment rates and type of repair. Methods: The study cohort included all men referred to a vascular network with a large abdominal aortic aneurysm (AAA). Basic demographic information, nurse assessment details, as well as outcome data were extracted from the national NAAASP IT system, AAA SMaRT, for analysis. Results: Some 3 026 men were referred for possible intervention (48% first screen, 52% surveillance). Some 448 men (13.3%) either declined (63, 2.1%), or were turned down for early intervention for various reasons (385, 12.7%). Some 8% were declined for medical reasons (true turn down rate). Men referred from surveillance were older, and more likely not to have had elective surgery within three months (16.0 vs. 11.2%; HR 1.37, 95% CI 1.07–1.75, p = .011). Turn down rates did not vary among local programmes, when surveillance men were taken into account. Some 2 624 (87%) men had planned AAA repair, with a peri-operative mortality of 1.3%. Thirty day surgical mortality was lower after EVAR: 0.4% compared with 2.1% after open repair. The method of repair remained consistent year on year, with roughly equal numbers undergoing endovascular (50%) and open surgical repair (48%); 2% unknown. There was regional variation in the proportion treated by endovascular repair: from 20% to 97%. Conclusion: The turn down rate after referral for treatment with a screen detected AAA was low, but there remains considerable regional variation in the proportion undergoing endovascular repair. Procedures were undertaken with low peri-operative mortality.